2022
DOI: 10.3390/cancers14194555
|View full text |Cite
|
Sign up to set email alerts
|

A Novel tiRNA-Gly-GCC-1 Promotes Progression of Urothelial Bladder Carcinoma and Directly Targets TLR4

Abstract: Background: Patients with urothelial bladder carcinoma (UBC) have a poor prognosis and a high risk of progression. Recently, tRNA-derived small RNAs (tsRNAs), a novel type of noncoding RNA, have been identified. In our previous study, we found tiRNA-Gly-GCC-1 was significantly upregulated in UBC tissue and might target the predicted target gene toll-like receptor 4 (TLR4) to play a regulatory role in UBC. Thus, the aim of this study was to identify the functional roles of tiRNA-Gly-GCC-1 and the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…progression of bladder cancer with downregulation inhibiting cell proliferation, migration, and invasion, promoting apoptosis, and affecting the cell cycle. 31 Similarly, Chen et al concluded that tRFphe-GAA-031 and tRF-VAL-TCA-002 are significantly upregulated in colorectal cancer (CRC) tissues and could be used as potential biomarkers and targets for intervention. 32 In the present study, we screened three tsRNAs in the tsRFun database according to Log2 Today, most studies have demonstrated that the action mechanisms of tsRNAs influence cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…progression of bladder cancer with downregulation inhibiting cell proliferation, migration, and invasion, promoting apoptosis, and affecting the cell cycle. 31 Similarly, Chen et al concluded that tRFphe-GAA-031 and tRF-VAL-TCA-002 are significantly upregulated in colorectal cancer (CRC) tissues and could be used as potential biomarkers and targets for intervention. 32 In the present study, we screened three tsRNAs in the tsRFun database according to Log2 Today, most studies have demonstrated that the action mechanisms of tsRNAs influence cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…39 According to previous studies, some tsRNAs can influence cancer progression through the protein sponge mechanism. 12,31 Tao et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzer bir araştırmada Qin ve ark. [71] tanımlanan yeni bir tiRNA-Gly-GCC-1'in, mesane kanserinin ilerlemesinde teşvik edici bir görevinin toll bezeri resöptörü TLR4'ü hedefleyerek yaptıgını ortaya çıkarmışlardır. tiRNA-Gly-GCC-1'in aşagı regülasyonu sonucunda ise, hücre çoğalması göçünü ve apoptozu teşvik edebileceğini gösterdiler.…”
Section: Tirna'lar Ve Kanserunclassified